2021
DOI: 10.3342/kjorl-hns.2020.00822
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intraoperative Neuromonitoring during Thyroidectomy with Transcutaneous Adhesive Skin Electrodes

Abstract: Background and Objectives Variable types of electrodes for intraoperative neuromonitoring (IONM) during thyroid surgery have been introduced to make up for the shortcomings of conventional endotracheal electromyogram tube. In this study, we sought to evaluate the efficacy of transcutaneous adhesive skin electrodes for IONM of recurrent laryngeal nerve (RLN) during thyroidectomy.Subjects and Method A total 97 nerves at risk of 80 patients were enrolled in this study. Two disposable adhesive skin electrodes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Prior research has demonstrated that the median amplitude of vagus nerve stimulation using the attached electrodes typically measures around 200 μV, which is less than that of the EMG tube. 15) Our current study yielded comparable results (Table 2), with the reduced intensity attributed to signal attenuation during the transmission of sig-nals from the vocal cord muscles to the skin.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Prior research has demonstrated that the median amplitude of vagus nerve stimulation using the attached electrodes typically measures around 200 μV, which is less than that of the EMG tube. 15) Our current study yielded comparable results (Table 2), with the reduced intensity attributed to signal attenuation during the transmission of sig-nals from the vocal cord muscles to the skin.…”
Section: Discussionsupporting
confidence: 76%
“…While previous research has examined the pre-and postoperative amplitude ratios of R1 to R2 and V1 to V2, 15) no prior studies have explored the connection between intraoperative nerve monitoring parameters and voice outcomes. In this study, we hypothesized that a larger difference in amplitude was associated with more severe nerve damage and worse voice change.…”
Section: Discussionmentioning
confidence: 99%